Mechanistic understanding of iron toxicity tolerance in contrasting rice varieties from Africa: 1. Morpho-physiological and biochemical responses - Onyango. D.A.; Entila, F.; Dida, M.M.; Ismail, A.M.; Drame, K.N. (Commonwealth Scientific and Industrial Research Organisation, 2019)
Iron (Fe) is a fundamental element involved in various plant metabolic processes. However, when Fe uptake is excessive, it becomes toxic to the plant and disrupts cellular homeostasis. The aim of this study was to determine the physiological and biochemical mechanisms underlying tolerance to Fe toxicity in contrasting rice varieties adapted to African environments. Four varieties (CK801 and Suakoko 8 (tolerant), Supa and IR64 (sensitive)) selected from our previous work were analysed in more detail, and the first part of this study reports morphological, physiological and biochemical responses induced by Fe toxicity in these four varieties. Morphological (shoot length, root length, number of lateral roots), physiological (photosynthesis rate, stomatal conductance, transpiration rate, fluorescence, relative water content and cell membrane stability) and biochemical (tissue Fe, chlorophyll pigments, soluble sugars, protein and starch) traits were measured, as appropriate, on both shoot and root tissues and at different time points during the stress period. Fe toxicity significantly (P ≤ 0.05) reduced growth and metabolism of all the four varieties. Tolerant varieties showed more lateral roots than the sensitive ones, under Fe toxic conditions as well as higher photosynthesis rate, chlorophyll content and cell membrane stability. Strong dilution of Fe concentration in cells was identified, as one of the additional tolerance mechanisms used by CK801, whereas Suakoko 8 mainly used strong mobilisation of carbohydrates at the early stage of the stress period to anticipate metabolite shortage. Traits associated with Fe toxicity tolerance in this study could be specifically targeted in trait-based breeding programs of superior lowland rice varieties tolerant of Fe toxicity.